A Hard Day's Night: Diel Shifts in Microbial Eukaryotic Activity in the North Pacific Subtropical Gyre - Hu, Sarah K.; Connell, Paige E.; Mesrop, Lisa Y.; Caron, David A. (Frontiers in Marine Science, 2018)
Molecular analysis revealed diel rhythmicity in the metabolic activity of single-celled microbial eukaryotes (protists) within an eddy in the North Pacific Subtropical Gyre (ca. 100 km NE of station ALOHA). Diel trends among different protistan taxonomic groups reflected distinct nutritional capabilities and temporal niche partitioning. Changes in relative metabolic activities among phototrophs corresponded to the light cycle, generally peaking in mid- to late-afternoon. Metabolic activities of protistan taxa with phagotrophic ability were higher at night, relative to daytime, potentially in response to increased availability of picocyanobacterial prey. Tightly correlated Operational Taxonomic Units throughout the diel cycle implicated the existence of parasitic and mutualistic relationships within the microbial eukaryotic community, underscoring the need to define and include these symbiotic interactions in marine food web descriptions. This study provided a new high-resolution view into the ecologically important interactions among primary producers and consumers that mediate the transfer of carbon to higher trophic levels. Characterizations of the temporal dynamics of protistan activities contribute knowledge for predicting how these microorganisms respond to environmental forcing factors.